CO-CREATION: LITERATURE REVIEW AND RESEARCH ISSUES - Dhaka, Sunishtha (International Journal of Research -GRANTHAALAYAH, 2015)
Co-Creation has attracted serious research attention in the recent past. Purpose of this paper is to review co-creation research, classify research articles according to the two approaches, content and process and on the basis of methodologies used in the articles and find the gaps in the literature for better co-creation research. A total of 110 articles from 53 refereed journals are classified into six categories on the basis of content approach: Value co-creation, co-creation, customer engagement, co-innovation, co-destruction and customer network. Research methodologies were classified into conceptual, empirical, descriptive, exploratory and experimental approaches. This study finds lacking in co-creation evaluation and implementation as well as better facilitation of co-creation value chain and processes. This paper could be helpful for business managers as well as for the firms to understand co-creation efficiency and to regain the customer’s satisfaction, trust and loyalty to facilitate customers to innovate and enhance competitive advantage.